An outpatient model of care for COVID‐19 infected kidney transplant patients – The hospital‐at‐home. Issue 5 (11th March 2023) - Liew, Ian Tatt; Tan, Woei Jen Michelle; Ho, Quan Yao; Chung, Shimin Jasmine; Thangaraju, Sobhana; Yong, Jinhua; Ng, Eleanor; He, Xia; Kwan, Natelie; Kee, Terence
Abstract: Background: The COVID‐19 pandemic is protracted and episodic surges from viral variants continue to place significant strain on healthcare systems. COVID‐19 vaccines, antiviral therapy and monoclonal antibodies have significantly reduced COVID‐19 associated morbidity and mortality. Concurrently, telemedicine has gained acceptance as a model of care and a tool for remote monitoring. These advances allow us to safely transit our inpatient‐based care for COVID‐19 infected kidney transplant recipients (KTRs) to a hospital‐at‐home (HaH) model of care. Methods: KTRs with PCR‐proven COVID‐19 infection were triaged by teleconsult and laboratory tests. Suitable patients were enrolled into the HaH. Remote monitoring via teleconsults were conducted daily until patients were de‐isolated based on a time‐based criterion. Monoclonal antibodies were administered in a dedicated clinic where indicated. Results: Eighty‐one KTRs with COVID‐19 were enrolled into the HaH between February and June 2022, 70 (86.4%) completed HaH recovery without complications. Eleven (13.6%) patients required inpatient hospitalization for medical issues ( n  = 8) and weekend monoclonal antibody infusion ( n  = 3). Patients requiring inpatient hospitalization had longer transplant vintage (15 years vs. 10 years, p  = .03), anaemia (haemoglobin 11.6 g/dL vs. 13.1 g/dL, p  = .01), lower eGFR (39.8 vs. 62.9 mL/min/1.73 m 2, p  < .05) and lower RBD levels (<50 AU/mL vs. 1435 AU/mL, p  = .02). HaH saved 753 inpatient patient‐days with no deaths observed. Hospital admission rates from the HaH programme was 13.6%. Patients who required inpatient care had direct access admission without utilization of emergency department resources. Conclusion: Selected KTRs with COVID‐19 infection can be safely managed in a HaH programme; alleviating strain on inpatient and emergency healthcare resources. Summary at a Glance: Home‐based recovery under telemonitored care (hospital‐at‐home programme) is a viable alternative to admission in select COVID‐19 infected kidney transplant recipients.